CALET results after three years on the International Space Station. (February 2020) - Asaoka, Y; Adriani, O; Akaike, Y; Asano, K; Bagliesi, M G; Berti, E; Bigongiari, G; Binns, W R; Bonechi, S; Bongi, M; Bruno, A; Buckley, J H; et al.
Abstract: The CALET (CALorimetric Electron Telescope) space experiment, which is currently conducting direct cosmic-ray observations onboard the International Space Station (ISS), is an all-calorimetric instrument optimized for cosmic-ray electron measurements with capability to measure hadrons and gamma-rays. Since the start of observation in October 2015, smooth and continuous operations have taken place. In this paper, we will give a brief summary of the CALET observations ranging from charged cosmic rays, gamma-rays, to space weather, while focusing on the energy spectra of electrons and protons.